Artificial Bee Colony for Minimizing the Energy Consumption in Mobile Ad Hoc Network - Tareq, M. (Springer Verlag, 2019)
Wireless ad hoc network is widely used nowadays, in particular the mobile type, known as the mobile ad hoc network (MANET). This type of network consists of sets of mobile nodes that do not require a fixed infrastructure such as an access point or base station. The common use of MANET is to enable nodes contacting in the absence of the typical communications infrastructure. Constantly changing topology and having no fixed infrastructures are some of the challenges confronted through a MANET designing. Hence, emphasizing the need to establish an efficient connection inside the network we use for a routing protocol to explore paths among nodes. The guarantee of finding optimum path formation among the nodes is the primary goal of the routing protocol, in order to ensure that messages would be delivered timely. The aim of this paper is to find the best possible route from the source to the destination based on a method inspired by the searching behaviour of bee colonies, i.e. artificial bee colony (ABC) algorithm. This algorithm works on minimizing the average energy consumption of the selected route. For evaluation purposes, the proposed model has been applied on two protocols, i.e. the Destination-Sequenced Distance-Vector Routing (DSDV) and Ad hoc On-demand Distance-Vector (AODV). The evaluation is based on node speed and packet size topology parameters. The results show that the network nodes can save more energy in AODV as compared to DSDV. As such, it can be concluded that optimizing the path from the source to the destination has a significant impact on the quality of the network performance. Â© 2019, Springer Nature Switzerland AG.